Analisis Implementasi P5 (Projek Penguatan Profil Pelajar Pancasila) Kurikulum Merdeka SD Negeri 27 Pangkalpinang. - Liadi, Rossy; Romadon; Yorenza Meifinda (Universitas Muhammadiyah Bangka Belitung, 2025)
This research aims to understand the planning and implementation carried out in the Project to Strengthen the Profile of Pancasila Students (P5) at SD Negeri 27 Pangkalpinang. This type of research uses a qualitative descriptive approach with data collection techniques through interviews, documentation, and triangulation. Data analysis employs the Miles and Huberman model, including data collection, data reduction, data presentation, and drawing conclusions and verification. The subjects consist of the principal, class teachers of grades 1-6, and a sample of students from grades 1-6. The research results on the planning and implementation stages of P5 indicate that the planning stage of P5 for the profile project for the 2023-2024 academic year has been well executed according to the P5 guidelines from the Ministry of Education and Culture. This begins with 1) understanding the independent curriculum, 2) understanding assessment and learning of the independent curriculum, 3) preparing the KOSP, 4) forming the P5 facilitator team, 5) identifying the school's readiness level, 6) determining themes, topics, dimensions, goals, and time allocation, 7) compiling the P5 module, and 8) designing the P5 reporting. However, improvements are needed in the P5 module as the school did not follow up on the action plan since they used the profile project flow 1. The implementation stage of P5 at SD Negeri 27 Pangkalpinang has been well-executed, including 1) conducting P5 activities according to the P5 module design and 2) the school holding P5 learning celebrations showcasing students' reflection results.